Clays and Clay Minerals, Vol. 55, No. 4, 348–353, 2007. - Okada, Tomohiko; Ehara, Yusuke; Ogawa, Makoto (The Clay Minerals Society, 2007)
The adsorption of Eu3+ from aqueous solution to natural Na+-montmorillonite (Kunipia F), synthetic saponite (Sumecton SA) and synthetic fluoro-tetrasilicic mica (Na+-TSM) clay samples was investigated. Adsorption capacities derived from the isotherms were 1.02, 0.71 and 1.00 meq/g of clay, respectively, for Kunipia F, Sumecton SA and Na+-TSM. The adsorption capacities were comparable to the cation exchange capacities of the clays, which were 1.19, 0.71 and 0.94 meq/g of clay, respectively. The greater slope of the TSM adsorption isotherm relative to the montmorillonite and saponite isotherms indicates a high affinity of Eu3+ forNa +-TSM. The high affinity of TSM forEu 3+ was thought to be related to the large electronegativity of the octahedral fluorine groups in TSM. Photoluminescence of adsorbed Eu3+ was observed for saponite and TSM, but not for montmorillonite. Quenching of Eu3+ luminescence by Fe in the montmorillonite structure is the probable reason for this phenomenon. The luminescence intensity varied with the amount of adsorbed Eu3+ forsaponite and TSM as a result of self-quenching.
Adsorption Of Eu3+ To Smectites And Fluoro-tetrasilicic Mica
Clays and Clay Minerals, Vol. 55, No. 4, 348–353, 2007. Adsorption Of Eu3+ To Smectites And Fluoro-tetrasilicic Mica. Tomohiko Okada; Yusuke Ehara; Makoto Ogawa. DOI: 10.1346/CCMN.2007.0550402. Copyright © 2007, The Clay Minerals Society
Keywords: Periodicals; Geology; Adsorption; Europium (III) Ion; Fluoro-tetrasilicic Mica; Kunipia F; Montmorillonite; Photoluminescence; Sumecton SA; Synthetic Saponite